2021
DOI: 10.1051/e3sconf/202129701044
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and microstructure evolution of high-manganese (0.9 C – 13.95 Mn) steel during aging

Abstract: The influence of temperature on the structural and mechanical properties of the (0.9 C - 13.95 Mn) steel was investigated in this work. The high-manganese steel has underwent aging treatments at temperatures 700, 750, 800 and 850 °C for different times. The experimental techniques used are hardness test, scanning electron microscopy, optical microscopy and X-ray diffraction. The mechanical behavior and microstructural evolution of the high-manganese steel during aging are almost the same. The aging of the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Owing to their importance at the industrial level, steels have been extensively studied to understand their metallurgical behavior [5][6][7][8][9][10]. In the literature, the phenomenon of austenite grain growth and its relationship with the temperature and time of the aging treatment have gained great interest [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their importance at the industrial level, steels have been extensively studied to understand their metallurgical behavior [5][6][7][8][9][10]. In the literature, the phenomenon of austenite grain growth and its relationship with the temperature and time of the aging treatment have gained great interest [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…At the level of scientific research, an attention has been paid to the assessment of the metallurgical behavior of the stainless steels, including their aging behavior [5][6][7][8][9]. At hightemperatures and for prolonged holding times, several studies demonstrated that the microstructure of the austenitic stainless steels undergoes changes as the increase of the grain size and the decrease in the area of grain boundaries per unit volume [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%